Claiming Home Migration Biographies and Everyday Lives of Queer Migrant Women in Switzerland - Büchler, Tina (Kultur und soziale Praxis, 2022)
Through biographical narratives, Claiming Home traces how queer migrant women living in Switzerland navigate often contradictory perspectives on sexuality, gender, and nation. Situated between heteronormative and racialized stereotypes of migrant women on the one hand, and the implicitly white figure of the lesbian on the other, queer migrant women are often rendered ›impossible subjects.‹ Claiming Home maps how they negotiate conflicting loyalties in this field and how they, in their own way, claim a sense of belonging and home.